The Effect of Perturbation-Based Balance Training and Conventional Intensive Balance Training on Reactive Stepping Ability in Individuals With Incomplete Spinal Cord Injury or Disease: A Randomized Clinical Trial - Unger, Janelle; Chan, Katherine; Lee, Jae W.; Craven, B. Catharine; Mansfield, Avril; Alavinia, Mohammad; Masani, Kei; Musselman, Kristin E. (Frontiers in Neurology, 2021)
Introduction: Impaired balance leads to falls in individuals with motor incomplete spinal cord injury or disease (iSCI/D). Reactive stepping is a strategy used to prevent falls and Perturbation-based Balance Training (PBT) can improve this ability. Objective: The objective of this study was to determine if PBT results in greater improvements in reactive stepping ability than frequency-matched Conventional Intensive Balance Training (CIBT) in adults with iSCI/D. Design: Randomized clinical trial. Setting: Tertiary SCI/D rehabilitation center. Participants: Twenty-one adults with chronic (>1 year) iSCI/D were randomized. Due to one drop out 20 participants completed the study. Methods: Participants were randomly allocated to complete either PBT or CIBT three times per week for 8 weeks. Both programs included challenging static and dynamic balance tasks, but the PBT group also experienced manual external balance perturbations. Main Outcome Measures: Assessments of reactive stepping ability using the Lean-and-Release test were completed at baseline, and after 4 and 8 weeks of training, and 3 and 6 months after training completion. A blinded assessor evaluated secondary outcomes. Results: Twenty-five participants were screened and 21 consented; one withdrew. Ten PBT and 10 CIBT participants were included in analyses. Across all participants there were improvements in reactive stepping ability (p = 0.049), with retention of improvements at follow up assessments. There were no differences in reactive stepping ability between groups [median (interquartile range): PBT 0.08 (0.68); CIBT 0.00 (0.22)]. One participant in the PBT group experienced a non-injurious fall during training. Conclusions: Balance training is beneficial for individuals with iSCI/D, but the addition of manual perturbations (i.e., PBT) did not prove advantageous for performance on a measure of reactive stepping ability. Clinical Trial Registration:www.ClinicalTrials.gov, identifier: NCT02960178.